Aplikasi Nanopartikel Perak dari Ekstrak Tumbuhan Sebagai Agen Antibakteri dalam Sediaan Gel dan Krim Wajah: Systematic Review - Syifa Nabilah Az-zahra; Pingkan Adinda Regita Putri; Ganjar Eko Prasetyo; Budiman Anwar (UIN Sunan Gunung Djati Bandung, 2026)
Green-synthesized silver nanoparticles (AgNPs) have emerged as promising antibacterial agents due to their high antimicrobial efficacy, good biocompatibility, and environmentally friendly synthesis process. This study aimed to analyze recent advances in the application of green-synthesized AgNPs incorporated into topical gel and cream formulations as antibacterial agents. A systematic review approach was employed by systematically searching the Scopus, ScienceDirect, PubMed, SpringerLink, and Google Scholar databases for English-language articles published between 2015 and 2025. The literature search was conducted from September 17 to October 22, 2025, using Boolean operators with the following keywords: (